2022
DOI: 10.3389/fmicb.2021.765113
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Carbapenem-Non-susceptible Pseudomonas aeruginosa Clinical Isolates From Saudi Arabia Revealed a Global Dissemination of GES-5-Producing ST235 and VIM-2-Producing ST233 Sub-Lineages

Abstract: Carbapenem-resistant P. aeruginosa has become a major clinical problem due to limited treatment options. However, studies assessing the trends in the molecular epidemiology and mechanisms of antibiotic resistance in this pathogen are lacking in Saudi Arabia. Here, we reported the genome characterization in a global context of carbapenem non-susceptible clinical isolates from a nationally representative survey. The antibiotic resistance profiles of the isolates (n = 635) collected over 14 months between March 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
3
8
0
Order By: Relevance
“…The presence of ESBLs genes ( bla OXA-1 , bla CTX-M-3 and bla OXA-232 ) in the K6 isolate is consistent with the phenotypic finding in which the isolate was highly resistant to third- and fourth-generations of cephalosporins. Consistent with our findings, Doumith et al [ 25 ] recently reported the presence of the plasmid p ColKP3 carrying bla OXA-232 in Pseudomonas aeruginosa clinical isolates from Saudi Arabia, which may indicate the exchange of plasmids among different microbial strains and the circulation of such plasmids in our region. ARGs residing in extrachromosomal plasmid DNA tend to disseminate more into different niches, and the replication initiator protein (Rep) is required for the replication initiation of this plasmid [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The presence of ESBLs genes ( bla OXA-1 , bla CTX-M-3 and bla OXA-232 ) in the K6 isolate is consistent with the phenotypic finding in which the isolate was highly resistant to third- and fourth-generations of cephalosporins. Consistent with our findings, Doumith et al [ 25 ] recently reported the presence of the plasmid p ColKP3 carrying bla OXA-232 in Pseudomonas aeruginosa clinical isolates from Saudi Arabia, which may indicate the exchange of plasmids among different microbial strains and the circulation of such plasmids in our region. ARGs residing in extrachromosomal plasmid DNA tend to disseminate more into different niches, and the replication initiator protein (Rep) is required for the replication initiation of this plasmid [ 26 ].…”
Section: Discussionsupporting
confidence: 92%
“…The overrepresentation of Pseudomonas spp. is consistent with previously reported bla GES-5 distribution 62 . Assembled contigs containing bla GES-5 varied dramatically in length (median=4,900bp, range=960-7,086,823bp), reflecting the fact that assembly of integron regions from short reads can lead to short contigs.…”
Section: A Historical and Global Dataset Of Bla Ges-5 Contigssupporting
confidence: 94%
“…To date, bla GES-5 has been linked to several clinical outbreaks in Japan 58 , Korea 59 , the UK 60 , and the Czech Republic 61 . Moreover, bla GES-5 has been identified globally across a range of species, both on the chromosome (most notably Pseudomonas aeruginosa ST235 62 ) and plasmids (for example, the Q-type plasmid pHPRU111 found across several Enterobacterales spp . 60 ).…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to third-generation cephalosporins, fluoroquinolones, and aminoglycosides has increased due to the spread of antimicrobial-resistant Gramnegative bacteria. In particular, the dramatic increase and spread of carbapenem-resistant-Gram-negative bacteria (CRGNB) has become a serious global public health concern, including in Saudi Arabia [5][6][7][8]. The World Health Organization (WHO) has classified CRGNB as a critical pathogen, indicating that it poses significant threats to human health and necessitates immediate research and development of novel antimicrobials [9][10][11].…”
Section: Introductionmentioning
confidence: 99%